Description of two new species of the Neoperla montivaga group (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region, China - Yang, Juan; Zhang, Sujiong; Li, Weihai (Zootaxa, 2017)
The following two new species from Shiwandashan of Guangxi Zhuang Autonomous Region, China are described, Neoperla bicolor Yang, Zhang & Li, sp. nov. and N. muranyii Yang, Zhang & Li, sp. nov. The new species are compared with related congeners of their respective species subgroups.